Elliott Kartler: capstone - Kartler, Elliott, artist (Colorado State University. Libraries, 2025)
The artist's statement: Studying fiber arts and graphic design side by side, I'm increasingly drawn to patterns and texture. Repeated patterns of unique shapes and illustrations create detailed textures on a surface. Overlaying multiple patterns amplifies this texture effect and invites viewers to stay longer and untangle the different elements. In a visually saturated era, I break the pattern by using pattern in a new way. While my planning process is messy, free-form, and pure creativity, my finished designs are carefully polished, measured, and spaced for an optimal viewing experience. I take pride in the organization and layout of my design work. I set rules for a project about the type, grids, and spacing of each element to create a consistent and pleasing design. I balance dense patterns and textures with enough white space so they aren't overwhelming. My time in fibers has taught me the value of working with my hands and physical materials. I carefully consider the materials and techniques I use in my work for both utility and symbolic qualities. In my fiber art and design work, I consider the tactile experience of the audience. Whether that is melted faux fur on a soft sculpture or constructing a cloth-wrapped hardcover for a book, the way my work feels is an integral part of my practice.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design